The transposed-word effect revisited: the role of syntax in word position coding. - Wen, Yun; Mirault, Jonathan; Grainger, Jonathan (Language, Cognition & Neuroscience, 2021)
Skilled readers may misinterpret "you that read wrong" for "you read that wrong": a transposed-word effect. This relatively novel finding, which supports parallel word processing during sentence reading, is attributed to a combination of noisy bottom-up word position coding and top-down syntactic constraints. The present study focussed on the contribution of syntactic constraints in driving transposed-word effects. In a speeded grammatical decision experiment, two types of ungrammatical transposed-word sequences were compared, namely a transposition either across a syntactic phrase ("the have girls gone home") or within a syntactic phrase ("the girls gone have home"). We found longer response times and lower accuracy rates for within-phrase transpositions than across-phrase transpositions, demonstrating a direct influence of syntactic structures on the transposed-word effect. We conclude that the assignment of words to positions in a sentence is guided by top-down syntactic constraints.